Relationship of Individual, Psychological and Organizational Factors with Practical Performance Professional Continuity Nurse in Non-Inpatient Room Intensive Regional General HospitalAceh Government Area 2022 - Muhammad Muhammad; Hajjul Kamil; Said Usman; Marthoenis Marthoenis; Elly Wardhani (Budapest International Research and Critics University, 2022)
This study aims to determine the relationship between the performance of the continuous professional practice of nurses with individual, psychological and organizational factors in the Non-Intensive Intensive Care Unit at the Regional General Hospital.Aceh governmentyear 2022. This research uses descriptive analytic method with cross sectional approach. Sampling through random sampling approach. The research subjects were 224 implementing nurses who served in thenon-intensive inpatient roominstallationp. Regional general hospitalAceh government. Measured variableage, gender, education, years of service, employment status and income, psychological factors consist of sub variablesmotivation and perception, while the organizational factors that are measured are the sub-variables of leadership and supervision. The instrument uses a Likert scale. Analysis of the data used is associative test using Chi-Square and multivariate test using Binner Logistic Regression to find the most dominant factor influencingrelationship with individual, psychological and organizational factors with continuous evaluation of the performance of the nurse's professional practice, with the help of a computer program. The results of the study with the Chi-Square correlation test showed that aand the relationship between the level of education, leadership and supervision with evaluationcontinuous performance of the nurse's professional practice,and there is no relationship between age, gender, employment status, years of service, income, perception and motivation with evaluationthe performance of the continuous professional practice of nurses, while the multivariate test showedthat nurses with a Nurse, Masters in Nursing and Nurse Sp 1 Nursing education have an evaluation valuecontinuous performance of the nurse's professional practicebetter than nurses with a Diploma III nursing education level, which is 0.5 times and based on the analysis, it was found that there was a significant relationship between education level and evaluation.continuous performance of the nurse's professional practice and leadership